On reliable communication in transmit-only networks for home automation. (1st January 2018) - Parsch, Philip; Masrur, Alejandro
Abstract: Home-automation applications such as intelligent illumination, heating, and ventilation allow reducing the overall energy consumption and improve comfort in our everyday lives. To implement such applications, multiple sensors and actuators often need to be connected into networks typically communicating over radio signals, i.e., wireless sensor networks (WSNs). Many available technologies are based on bidirectional devices with the capability of acknowledging packets and performing retransmissions if necessary. However, home-automation devices mostly report data to a sink for which they do not need any feedback channel or external control, thus, unidirectional devices can be used instead reducing costs and energy consumption. On the other hand, since unidirectional nodes are unable to perform carrier sensing or acknowledge packets, the resulting networks are often unreliable. To overcome this problem, we propose a medium access control (MAC) that consists in making each transmit-only node send a sequence of redundant packets. The proposed method guarantees reliability, i.e., at least one packet of each sequence reaches its destination within a specified deadline by carefully selecting inter-packet times. In contrast to similar approaches from the literature, our MAC is based on a more general model that allows describing arbitrary deadlines and packet sizes for each node in the network and can accommodate considerably more nodes into a reliable network as the ratio between the longest and the shortest deadline increases. We illustrate these and other benefits of the proposed MAC by means of extensive simulations based on the OMNeT++ framework.